Numerical simulation of thin layer coffee drying by control volumes (2010)
ABSTRACT: The thin layer drying model proposed by Sokhansanj and Bruce (1987) was implemented to model the drying process of parchment coffee beans. A computational model based on a control volume approach was developed to simulate the drying process of parchment coffee. A one dimensional transient analysis was implemented in the radial direction applied to a spherical coffee bean of equivalent radius. The results found that, even though the numerical value for the mass transfer coefficient is a small number (about of 10⁷ m/sec), moisture content predictions were sensitive to this value. The predicted drying curve compared favorably with published results.